ERROR ANALYSIS OF JAPANESE PASSIVE SENTENCE COMPREHENSION IN WRITTEN VARIANT AMONG STUDENTS OF JAPANESE LANGUAGE AND CULTURE STUDY PROGRAM AT UNSADA - Andi Irma Sarjani; Juariah, Aisyah Rasuna Syamsi (International Journal of Teaching and Learning, 2024)
This study discusses the "Analysis of Passive Sentences Comprehension Errors in Written Japanese Language of UNSADA Students of the Japanese Language and Culture Program". This study aims to determine the level of student understanding in comprehending Japanese passive sentences, describe the errors in comprehending Japanese passive sentences, and describe the factors causing language errors in Japanese passive sentences. The method used in this study is a quantitative descriptive method. The respondents of this study were UNSADA students of the Japanese Language and Culture program in 2016 and 2017. The results showed that the average score of respondents in comprehending Japanese passive sentences of UNSADA students of the Japanese Language and Culture program in 2016 and 2017 was 58.8 out of 60 respondents. Thus, it can be said that they do not understand about Japanese passive sentences, so it can be said that the level of understanding of the respondents is still low. The errors can be categorized as intralingual errors, which are in the form of Overgeneralization errors and Development Errors. This is due to being influenced by the mother tongue (B1), the respondents' lack of knowledge about Japanese passive sentences, and the respondents' lack of accuracy when answering the questionnaire questions.